Simulation of hydraulic fracturing in tight formations - Sarmadivaleh, Mohammad; Rasouli, Vamegh (Australian Petroleum Production and Exploration Association, 2010)
Production from tight formations is becoming a main focus around the world and particularly in Australia. Hy¬draulic fracturing is one of the commonly used approaches to stimulate production from tight reservoirs. A good un-derstanding of mechanical properties of formation and the in-situ stresses is essential for a hydraulic fracturing study. In this work, using the log based approach, the me¬chanical properties and in-situ stresses were estimated in a tight gas formation. This data is then used as input for 2D numerical simulation of hydraulic fracturing in particle flow code (PFC). The initiation and propagation of an induced fracture was studied by increasing the rock strength to simulate a tight formation response. Thereaf¬ter, the model was divided into two zones to investigate the fracture containment capacity to simulate a fracture intersecting an interbed with formation properties being different on the two sides. The formation bond strength was increased on one side of the interbed and fracture extension was monitored. The results of both simulations showed how, by increasing formation strength equivalent to a tighter formation, the fracture extension ability re¬duces and the interbed containment capacity increases. The results were compared with some of the analytical models and good agreement was observed.